Risky policies: Local contestation of mainstream flood risk management approaches in Ireland. (November 2017) - Revez, Alexandra; Cortes-Vazquez, Jose A; Flood, Stephen
In 2017, the idea that floods are exceptional and temporary episodes is a conviction increasingly contradicted by their growing incidence and severity across the globe. Floods have lasting consequences for affected populations and such effects can be wide-ranging depending on local context. However, prevailing misconceptions remain concerning the nature and effect of floods on populations. The advent of risk-based approaches is arguably responsible for a distinct managerial perspective on floods, which often undermines the local contexts and the impacts central to these experiences. This is observable in Ireland, the case study site for this article, where policy transitions into risk-based approaches are increasingly leading to growing discontent regarding the manner in which flooding and community vulnerabilities are represented. The matter is further complicated by the interplay between risk and conservation policy. This paper considers how these powerful discourses shape ideas and decisions around flooding. Using narrative-based data, centred on a case study in the west of Ireland, we explore the understanding and perception of flood risk and nature conservation by local communities and contrast these with the views expressed through managerial approaches linked to flood risk management and conservation. By bringing together these three distinct positions (i.e. the flood risk management approach, conservation practice and local narratives) we have found limitations in underlying assumptions informing current flood risk management approaches and we bring to light crucial human dimensions of flooding which, we argue, are consistently diluted and/or buried by fractured representations of environmental and social dynamics.